A Delay Almost Periodic Competitive System in Discrete Time - Ronghua Tan; Lvli Liao (Discrete Dynamics in Nature and Society)
A discrete almost periodic competitive system with delay is proposed and analyzed. The system admits a unique almost periodic solution, which is shown to be uniformly asymptotically stable by using the method of Lyapunov function. Some specific numerical examples are provided to verify our analytical results.